Development of Student Worksheets Using Problem Based Learning Models on Algebraic Computing Operation Materials - Puri, Geby Karunila; Amri, Zulfi (Lembaga Riset Mutiara Akbar, 2022)
The formulation of the problem in this study are: How is the LKPD Development using a problem-based learning learning model on the Algebraic Computing Operation material? How is the validity of the Student Worksheet with the problem-based learning model developed as a learning medium for students? How are students' responses to the Worksheet Students by using a problem-based learning model? This study aims to produce a Student Worksheet product using a Problem Based Learning model on valid and feasible algebraic arithmetic operations. This research is a type of development research and uses 4-D (four-D) research procedures which are modified into 3-D (three-D), namely the definition stage, the design stage, and the development stage. The results of this study: 1) Researchers have produced Student Worksheets using the Problem Based Learning model on algebraic arithmetic operations on the subject of addition, subtraction, multiplication, and division in algebraic form. 2) the results of the assessment of the Student Worksheets from material experts are 94.3% with a very valid validity level and the assessment of the Student Worksheets from media experts is 81.6% with a fairly valid validity level. 3) obtaining the results of the assessment through a student questionnaire with an average percentage of 88.25% with a very positive category. From the results of the assessment of material experts, media experts, and student responses, the developed Student Worksheets are valid and suitable to be used as learning media by students.